2014
DOI: 10.1111/jace.12912
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Highly (100)‐Oriented SrTiO3 Thin Films on Si(111) Substrates Without Buffer Layer

Abstract: The SrTiO3 (STO) thin films were directly grown on Si(111) substrates without buffer layer by an electron‐cyclotron‐resonance ion beam sputter deposition. The growth temperature was varied from 700°C to 850°C, while other parameters were kept unchanged. X‐ray structural analysis demonstrates that the growth temperature has a strong influence in tuning degree of (100) orientation. The STO film grown at 800°C is found to be the highest degree of (100) orientation (98%) and a strong (100) fiber texture. For the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…4,6,10 It is therefore still highly desired to obtain BiFeO 3 lms with a certain orientation using a simple sol-gel process on the conventional silicon wafers, which are widely used in modern electronic industry. [11][12][13] Certainly, some studies have been done about the sol-gel processing of textured BiFeO 3 thin lms. 14 For example, Chang et al reported (001)-oriented BiFeO 3 on a glass substrate by reducing the thickness of Pt electrode via sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,10 It is therefore still highly desired to obtain BiFeO 3 lms with a certain orientation using a simple sol-gel process on the conventional silicon wafers, which are widely used in modern electronic industry. [11][12][13] Certainly, some studies have been done about the sol-gel processing of textured BiFeO 3 thin lms. 14 For example, Chang et al reported (001)-oriented BiFeO 3 on a glass substrate by reducing the thickness of Pt electrode via sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a lot of results have shown a strong link between the orientation and microstructure of the films and tunability . The control of the film orientation can be obtained by different ways: deposition parameters, nature of the substrate (or bottom electrode), or introduction of a buffer layer . In this investigation, we have chosen this latter option for the film orientation control.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The control of the film orientation can be obtained by different ways: deposition parameters, 14,15 nature of the substrate (or bottom electrode) 16 , or introduction of a buffer layer. [17][18][19] In this investigation, we have chosen this latter option for the film orientation control. In fact, the choice to introduce a buffer layer has been made for various reasons: this approach is independent of the substrate, the growth temperature (or postannealing treatment) can be decreased while maintaining a crystalline quality, and the tunability is very sensitive to strain.…”
Section: Introductionmentioning
confidence: 99%
“…SrTiO 3 thin films have been prepared on Si substrates by several vacuum techniques, such as molecular beam epitaxy (MBE), [10][11][12][13][14][15][16] sputtering, 21 pulsed laser ablation, 22 physical vapour deposition (PVD) 23 and electron-cyclotron-resonance ion beam sputter deposition. 24 A deep understanding on the growth mechanisms, interfacial layer properties and the effect of buffer layers on the structure of SrTiO 3 has been achieved through the use of these techniques. Solution-based methods, based on metalorganic decomposition (MOD) processes offer a versatile and low-cost alternative to vacuum techniques, as they are capable of producing crystalline deposits of a wide range of perovskite materials on large areas with uniform composition and thickness.…”
Section: Introductionmentioning
confidence: 99%